The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fmed.2018.00080
|View full text |Cite
|
Sign up to set email alerts
|

Spondyloarthritis, Acute Anterior Uveitis, and Fungi: Updating the Catterall–King Hypothesis

Abstract: Spondyloarthritis is a common type of arthritis which affects mostly adults. It consists of idiopathic chronic inflammation of the spine, joints, eyes, skin, gut, and prostate. Inflammation is often asymptomatic, especially in the gut and prostate. The HLA-B*27 allele group, which presents intracellular peptides to CD8+ T cells, is by far the strongest risk factor for spondyloarthritis. The precise mechanisms and antigens remain unknown. In 1959, Catterall and King advanced a novel hypothesis explaining the et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 224 publications
0
21
0
3
Order By: Relevance
“…This is the first direct evidence implicating gut fungal microbiome dysbiosis in UVT, and it supports a few earlier investigations that provided clues of the involvement of the fungal microbiome in ocular diseases like UVT. 17,18 The relevance of the observed dysbiosis in UVT patients would be all the more meaningful if functional attributes were associated with the genera that decreased or were enriched in UVT patients. Enrichment of five of the nine fungal genera in UVT patients was on expected lines since the enriched organisms like Aspergillus gracilis, Candida glabrata, Malassezia globosa, and M. restricta were opportunistic pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first direct evidence implicating gut fungal microbiome dysbiosis in UVT, and it supports a few earlier investigations that provided clues of the involvement of the fungal microbiome in ocular diseases like UVT. 17,18 The relevance of the observed dysbiosis in UVT patients would be all the more meaningful if functional attributes were associated with the genera that decreased or were enriched in UVT patients. Enrichment of five of the nine fungal genera in UVT patients was on expected lines since the enriched organisms like Aspergillus gracilis, Candida glabrata, Malassezia globosa, and M. restricta were opportunistic pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Few studies have demonstrated an increased immune sensitivity to fungal antigens in UVT implying that these fungal antigens may be an important risk factor of idiopathic UVT, especially for those associated with spondyloarthritis and multiple sclerosis. 17 In addition, Zárate-Bladés et al, 18 who had characterized only the bacterial populations, failed to identify the antigenic mimic that triggers UVT in the mice model of spontaneous UVT thus implying that other microbial communities including fungi may help to identify the trigger for UVT. Recently we showed association of gut fungal microbiome with bacterial keratitis.…”
mentioning
confidence: 99%
“…Due to improved microbe detection techniques, many groups now report finding Malassezia within the body of both healthy adults and immunocompetent patients with various ailments (1416, 2325, 33, 5261). Malassezia 's potential role in diseases of internal organs is just coming to light (19, 54, 6264). It is important to note that Malassezia 's presence is not synonymous with disease: in the vast majority of individuals, Malassezia colonize the body without causing symptoms.…”
Section: Malassezia Primermentioning
confidence: 99%
“…If Malassezia are involved in diseases of internal organs, AIDS would be expected to precipitate such diseases in genetically susceptible individuals—similarly to how it precipitates SD by allowing Malassezia to over proliferate on the skin. Interestingly, recent studies (reviewed in the next two sections) implicate Malassezia in arthritis (62) and demyelination (19), two common AIDS symptoms where no secondary infections were thought to be present.…”
Section: Malassezia Primermentioning
confidence: 99%
“…Up to 70% of AS patients have subclinical gut inflammation and 5-10% of these patients have more severe intestinal inflammation that progresses to clinically defined IBD (7). As intestinal dysbiosis has been increasingly linked to IBD in recent years (8-10), it is reasonable to speculate a close link between gut microbiota and AS development (3,11). Previous works have shown that the patients and transgenic rat model of AS had increased immunoglobulins G (IgG) or pro-inflammatory cytokines in response to bacterial products such as outer membrane protein and lipopolysaccharide (LPS) (12,13).…”
Section: Introductionmentioning
confidence: 99%